Notes on the situation of the educational system in the prelature of Ayaviri - Neira del Ben, Paul (2007)
In the present study, the educational situation in the territory of the prelature of Ayaviri is analyzed considering variables such as quality, efficiency and equity for the levels of initial, primary and secondary education. The study presents in general terms the current state of educational coverage and efficiency, literacy levels, learning achievements and other factors that contribute to a better understanding of the educational situation in that southern Andean region.